A new natricine snake of the genus Amphiesma (Squamata: Colubridae: Natricinae) from the central Truong Son, Vietnam - Ziegler, Thomas; Quyet, Le Khac (Zootaxa, 2006)
A new species of Amphiesma is described from the Truong Son (Annamite mountain range) of Quang Binh Province in central Vietnam. This new species is characterized by the combination of the distinct coloration and pattern, the slender body and tail (tail/total length ratio 0.31), the large eye diameter, a single loreal and preocular, three postoculars, a single anterior and posterior temporal, nine supralabials (fourth to sixth reach the eye), nine infralabials, 179 ventrals (plus two preventrals), anal plate divided, 99 divided subcaudals, dorsal scales in 19-19-17 keeled rows, 34 maxillary teeth (the two posteriormost enlarged), hemipenis simple, with undivided sperm groove, covered with small spines except for a single, strongly enlarged spine next to the sperm groove at the hemipenis base and except for irregularly arranged medium-sized spines that encircle the organ horizontally at the trunco-pedicel area. The new taxon is known only from a single male specimen that was collected in a limestone forest valley.